Conclusion: Outlook for coastal transitions - Heidkamp, C. Patrick; Morrissey, John; Morrissey, John (Towards Coastal Resilience and Sustainability, 2018)
Globally, rapid demographic change of coastal urban agglomerations, the speed of urbanisation over time, the overall impact of coastal space occupation as well
Keywords: Climate change; Coastal ecosystems; Coastal zones; Demographic changes; Economics; Ecosystem services; Ecosystems; Energy availability; Flood control; Impervious surface; Long term process; Sea level; Topography; Urban agglomerations; Urban development; Urban growth; dept.egm